2021
DOI: 10.1016/j.euo.2019.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Progression-directed Therapy for Oligoprogression in Castration-refractory Prostate Cancer

Abstract: In metastatic hormone-sensitive prostate cancer (mHSPC) the sensitivity to castration will eventually disappear due to selection of castration-resistant clones, so the patient progresses to metastatic castration-refractory prostate cancer (mCRPC). Median survival in mCRPC is approximately 35 mo [1], depending on different prognostic factors and the use of second-and third-line systemic treatment regimens, which come with a non-negligible financial cost and toxicity [2]. Clinical and iconographic progression (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 10 publications
(9 reference statements)
2
34
0
Order By: Relevance
“…Additionally some patients presented with progression among ADT at PSMA ligand staging and must be considered as early castration-resistant. Data about RT as MDT on this oncological situation are rare, although Berghen et al recently yielded first information that RT substantially postponed next-line systemic treatment [32]. In general the definition of oligometastases for prostate cancer is controversial and there is no general agreement between different experts panels [13,33].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally some patients presented with progression among ADT at PSMA ligand staging and must be considered as early castration-resistant. Data about RT as MDT on this oncological situation are rare, although Berghen et al recently yielded first information that RT substantially postponed next-line systemic treatment [32]. In general the definition of oligometastases for prostate cancer is controversial and there is no general agreement between different experts panels [13,33].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data support this hypothesis [8][9][10][11][12][13][14][15][16][17][18][19]. Our research group recently published promising results on the use of PDT in this setting, with a next-line systemic treatment-free survival (NEST-FS) of 21 months [20].…”
Section: Introductionmentioning
confidence: 85%
“…Based on the number of eligible patients we expect to recruit 18 patients in one year, for which a follow-up of at least 24 months will be necessary (median NEST-FS in the PDT group was 21 months in our retrospective trial [20].…”
Section: Data Analysis Sample Size Calculationmentioning
confidence: 99%
“…In contrast, cRT for mCRPC seems less attractive because the value of local therapy at such a late stage is questionable. Several retrospective studies show that radiotherapy to oligoprogressive sites could delay disease progression in mCRPC [22,24,28]. In the study by Yildirim et al, prolonged abiraterone use was also observed in mCRPC patients receiving prostate-directed therapy, but no signi cant improvement of OS was found (24.1 vs. 21.4 months; P = 0.08) [23].…”
Section: Discussionmentioning
confidence: 99%